Cellular analysis in bronchoalveolar lavage: inherent limitations of current standard procedure. Issue 6 (1st June 2017) - Bollmann, Benjamin-Alexander; Seeliger, Benjamin; Drick, Nora; Welte, Tobias; Gottlieb, Jens T.; Greer, Mark
Bronchoalveolar lavage (BAL) is an established procedure for diagnosing respiratory infections and characterising non-infective lung diseases [1]. Increasingly, emphasis has been placed on BAL cellular composition in the diagnostic algorithms for interstitial lung disease [2] and chronic lung allograft dysfunction following lung transplantation [3]. The "dead-space" concept: bronchoscope size and instillation protocol significantly alter BAL cellular composition http://ow.ly/ZEaj30be7HV